Method for modifying buried interface of perovskite solar cell

By using potassium stannate (PS) as the interface modification layer in perovskite solar cells, the non-radiative energy loss caused by oxygen vacancies on the surface of SnO2 and the base defects of the perovskite film are solved, and the photovoltaic performance of the device is significantly improved.

CN119866156AActive Publication Date: 2025-04-22INST OF MATERIALS HENAN ACAD OF SCI +1

Patent Information

Application Number
CN202510013867.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-22
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

In perovskite solar cells (PSCs), oxygen vacancies defects on the surface of SnO2 and structural defects on the bottom of the perovskite film lead to non-radiative energy loss, reducing the photoelectric conversion performance of the device.

Method used

Potassium stannate (PS) was used as the SnO2/perovskite interface modification layer, and the PS aqueous solution was coated on the SnO2 film by spin coating, and annealing was performed to form a potassium stannate interface modification layer to passivate the oxygen vacancy on the surface of SnO2 and the defects at the bottom of the perovskite film.

Benefits of technology

Through the introduction of the PS modification layer, interface recombination is effectively suppressed, charge transmission is promoted, photovoltaic performance of PSCs is significantly improved, and energy conversion efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866156A_ABST
    Figure CN119866156A_ABST
Patent Text Reader

Abstract

The invention discloses a method for modifying a buried interface of a perovskite solar cell, and the method specifically comprises the following steps: 1) dissolving potassium stannate powder in deionized water to prepare an aqueous solution with the concentration of 1-5mg / mL, and filtering the aqueous solution; 2) coating the aqueous solution on a tin dioxide thin film by adopting a spin-coating method; and 3) annealing the tin dioxide film coated with potassium stannate to form a potassium stannate interface modification layer. Compared with the prior art, the method has the advantages that PS is used as a SnO2 / perovskite interface modification layer, stannate ions can passivate oxygen vacancies on the surface of SnO2, surface defects of SnO2 are reduced, and accumulation and compounding of electrons between interfaces are inhibited by balancing the energy level between SnO2 and perovskite. K < + > promotes high-quality perovskite crystallization and reduces grain boundary defects; a-site cation vacancy is filled, the crystal structure stability of perovskite is enhanced, a more stable crystal phase is formed, the quality of the perovskite film is improved, and the device performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a method for modifying the buried interface of perovskite solar cells (PSCs), which aims to optimize the device structure and improve the photoelectric conversion performance of the device by introducing potassium stannate (PS) as an interface modification layer. Background Art

[0002] As a clean and renewable energy source, photovoltaic technology plays a key role in addressing climate change and achieving sustainable development. Organic-inorganic hybrid perovskite solar cells (PSCs) have attracted much attention due to their unique optoelectronic properties, low-cost preparation process and excellent defect tolerance, and are regarded as an important development direction after the third-generation photovoltaic technology. In recent years, the certified energy conversion efficiency of PSCs has exceeded 26.7%, which is comparable to commercial single-crystalline silicon cells, showing broad application prospects. However, this efficiency value is still a certain distance from the theoretical Shockley-Queisser limit (30.5%) of single-junction PSCs. Optimizing the device structure and improving the performance of the functional layer are the keys to achieving further efficiency improvement. In PSCs devices, tin dioxide (SnO2) is a commonly used electron transport layer (ETL) material. Compared with titanium dioxide (TiO2) and zinc oxide (ZnO), it has higher electron mobility and better energy level matching, which is conducive to promoting interfacial charge transfer and improving device efficiency. However, oxygen vacancy defects on the SnO2 surface will capture photogenerated charge carriers and induce non-radiative energy loss at the SnO2 / perovskite interface, thereby reducing the photoelectric conversion performance of the battery. Therefore, how to effectively alleviate the negative impact of SnO2 defects on device performance is a key issue that needs to be solved urgently.

[0003] To this end, researchers have proposed a variety of SnO2 interface passivation strategies, including the introduction of alkali metal cations or functional anions. For example, Gao (GAO D, YANG L, MA X, et al. Passivating Interface with Multifunctional Ionic Liquid Containing Simultaneously Fluorinated Anion and Cation Yielding Stable Perovskite Solar Cells over 23% Efficiency [J]. Journal of Energy Chemistry, 2022, 69: 659-666.) et al. introduced 4-fluoro-phenylammonium tetrafluoroborate (FBABF4) at the interface between SnO2 and perovskite, using BF4 -The method of forming coordination bonds with the SnO2 surface suppresses oxygen vacancy defects and promotes charge transfer; Zhu (ZHU S, WU J, SUN W, et al. Interlayer Modification Using Phenylethylamine Tetrafluoroborate for Highly Effective Perovskite Solar Cells [J]. ACS Applied Energy Materials, 2022, 5 (1): 658-666.) et al. introduced a molecular modification layer of phenylethylamine tetrafluoroborate (PEABF4) at the ETL / perovskite interface to promote electron extraction and passivate interface defects, thereby suppressing non-radiative carrier recombination. In addition, the structural defects at the bottom of the perovskite layer are also potential non-radiative recombination centers, especially in films prepared by the two-step method. To this end, the researchers developed a buried interface engineering strategy to regulate the energy level arrangement and defect distribution between the transport layer and the active layer by embedding an interface modification layer, thereby achieving comprehensive optimization of charge transport and device performance. For example, Wu (WU S, ZHANG J, LI Z, et al., Modulation of Defects and Interfaces Through Alkylammonium Interlayer for Efficient Inverted Perovskite Solar Cells. Joule, 2022, 4, 1248-1262.) et al. used a large chain alkyl ammonium interlayer (LAI) to reduce the energy loss between the transport layer and the perovskite, which not only suppressed the non-radiative recombination at the interface, but also improved the charge selectivity and extraction efficiency, making the device PCE exceed 22%. Xu (XU H, MIAO Y, WEI N, et al., CsI Enhanced Buried Interface for Efficient and Uv-robust Perovskite Solar Cells. Advanced Energy Materials, 2021, 12, 2103151.) et al. used CsI-SnO2 composite materials as ETL to promote the growth of perovskite films and effectively passivate interface defects. Cs + The gradient distribution optimizes the band alignment and significantly improves the efficiency of FAPbI3-based PSCs to 23.3%.

[0004] Given the significant effect of buried interface engineering in improving device performance, it is crucial to find a modifying molecule that can simultaneously eliminate oxygen vacancies on the SnO2 surface and defects at the bottom of the perovskite film. Summary of the invention

[0005] In order to solve the problem that the bottom surface defects of the perovskite film and the oxygen defects on the surface of the electron transport layer SnO2 reduce the performance of PSCs, the present invention proposes a method for modifying the buried interface of perovskite solar cells, by introducing potassium stannate (PS) as the SnO2 / perovskite interface modification layer into the PSCs device structure, and simultaneously passivating the oxygen defects on the SnO2 surface and the bottom defects of the perovskite film, thereby further improving the performance of PSCs.

[0006] The present invention adopts the following technical solutions to achieve the above-mentioned purpose:

[0007] A method for modifying the buried interface of a perovskite solar cell comprises the following steps:

[0008] 1) Prepare a solution: dissolve potassium stannate powder in deionized water to prepare an aqueous solution with a concentration of 1-5 mg / mL, and filter;

[0009] 2) coating: coating the aqueous solution on the tin dioxide film by spin coating;

[0010] 3) Annealing to form an interface modification layer: The tin dioxide film coated with potassium stannate is annealed to form a potassium stannate interface modification layer.

[0011] Wherein, the potassium stannate structural formula is:

[0012]

[0013] As a preferred embodiment, in step 1), the potassium stannate powder is added to deionized water, stirred at room temperature for 0.5 h, and filtered using a 0.22 μm filter membrane to obtain an aqueous solution.

[0014] As a preferred solution, the spin coating parameters of the spin coating method in step 2) are 3500-4500 rpm, 40-60 s.

[0015] As a preferred solution, the annealing treatment temperature in step 3) is 100° C. and the time is 10 min.

[0016] As a preferred solution, the method further includes preparing a perovskite active layer, a hole transport layer and a metal electrode on the tin dioxide film.

[0017] As a preferred solution, the perovskite active layer is prepared by a two-step method.

[0018] The PS interface modification layer can passivate the oxygen vacancies on the SnO2 surface, reduce the surface defects of SnO2, balance the energy levels between SnO2 and perovskite, and inhibit the accumulation and recombination of electrons at the interface. At the same time, potassium ions (K+) can promote the crystallization of perovskite, reduce grain boundary defects, fill the A-site cation vacancies, and enhance the crystal structure stability of perovskite.

[0019] Compared with the prior art, the present invention has the following advantages: PS is used as the SnO2 / perovskite interface modification layer, and the stannate ions can passivate the oxygen vacancies on the SnO2 surface, reduce the surface defects of SnO2, and inhibit the accumulation and recombination of electrons at the interface by balancing the energy levels between SnO2 and perovskite. + Promote the crystallization of higher quality perovskites and reduce grain boundary defects; fill A-site cation vacancies, enhance the crystal structure stability of perovskites, form a more stable crystal phase, improve the quality of perovskite films, and further enhance device performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The conductivity of the SnO2 film in the control group and the SnO2-PS film in the experimental group of the present invention.

[0021] Figure 2 The transmission spectra of the SnO2 film and SnO2-PS film on the ITO substrate of the present invention are shown in FIG.

[0022] Figure 3 Surface SEM images of the control group and PS-modified perovskite films of the present invention. DETAILED DESCRIPTION

[0023] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0024] A method for modifying the buried interface of a perovskite solar cell, the specific implementation formula and steps are as follows.

[0025] 1. Solution preparation:

[0026] Electron transport layer: The SnO2 colloidal solution (12 wt%) was diluted with deionized water to a ratio of 1:3, stirred at room temperature for 30 minutes, and then filtered through a syringe and a filter membrane to obtain the desired SnO2 solution.

[0027] Perovskite film: 599.3 mg of PbI2 powder was dissolved in 900 μL of DMF and 100 μL of DMSO, stirred at 70 °C for 3 hours, and then filtered through a syringe and a filter to obtain the desired PbI2 solution. In addition, 90 mg of FAI and 12 mg of MACl were dissolved in 1 mL of isopropanol (IPA) and stirred at room temperature for 30 minutes. Then the desired organic salt solution was obtained by filtering through a syringe and a filter.

[0028] Hole transport layer: First, take 520 mg of Li-TFSI in 1 ml of acetonitrile, then weigh 72.3 mg of Spiro-OMeTAD, take 17.5 μL of Li-TFSI acetonitrile solution and 29 μL of 4-tBP and mix them in 1 ml of chlorobenzene, and filter through a syringe and a filter membrane to obtain the required hole transport layer solution.

[0029] PS modification layer solution: Dissolve 0-8 mg PS powder in 1 mL of deionized water and stir at room temperature for 0.5 h until completely dissolved.

[0030] 2. Device preparation process:

[0031] 1. Cleaning of ITO glass: Wipe the ITO glass substrate with a detergent, and then ultrasonically clean it in deionized water, acetone and IPA for 30 minutes in sequence.

[0032] 2. Preparation of electron transport layer: In air environment, SnO2 thin film was prepared on the substrate by spin coating process at 3000 rpm for 50 seconds, and then heat treated at 150°C for 25 minutes.

[0033] 3. Preparation of PS buried interface modification layer: In air environment, PS modification solution (80 μL) was coated on the SnO2 film by spin coating process at 4000 rpm for 50 seconds, and then heat treated at 100°C for 10 minutes.

[0034] 4. Preparation of perovskite active layer: In a nitrogen environment, first spin-coat the PbI2 mixed solution (70 μL, 2000 rpm, 30 s), heat treat at 70 °C for 1 minute and cool for 10 minutes, then spin-coat 70 μL of FAI+MACl solution (1800 rpm, 30 s), and finally heat treat at 150 °C for 30 minutes in an air environment with a humidity of 30%-40%.

[0035] 5. Preparation of hole transport layer: In a nitrogen environment, the Spiro-OMeTAD solution (50 μL) was coated on the perovskite film using a spin coating process at 3000 rpm for 30 seconds.

[0036] 6. Preparation of gold electrode: at 5x10 -4 In a vacuum environment of 1.3 Pa, a 80nm thick metal electrode was deposited by thermal evaporation process.

[0037] 3. Preparation process of the control group device:

[0038] The preparation of the PS buried interface modification layer in step (3) is not performed, and the remaining steps are consistent with the device preparation process.

[0039] 4. Performance test:

[0040] 1. SnO2 film conductivity test:

[0041] In order to evaluate the effect of PS modification on the conductivity of SnO2 thin films, ITO / SnO2 / Au and ITO / SnO2 / PS / Au diode structures were used, and the conductivity of the film was calculated by measuring the current-voltage curve in the voltage range of -1 to 1V. The conductivity can be calculated using the following formula:

[0042]

[0043] Where ó represents conductivity, I is current density, L is the thickness of SnO2 film, V is the voltage inside the device, and S is the cross-sectional area of ​​the device.

[0044] like Figure 1 As shown in the figure, the conductivity of the control SnO2 film and the experimental SnO2-PS film is calculated to be 2.30×10-3 and 3.23×10-3S cm-1, respectively. The enhancement of conductivity is mainly due to the interaction between stannate ions and SnO2, which reduces oxygen vacancies, thereby improving charge transfer efficiency and enhancing device performance.

[0045] 2. SnO2 thin film light transmittance test:

[0046] In order to prove that the introduction of PS modification layer will not hinder the absorption of perovskite film in the visible light region, the light transmittance of the control SnO2 film and the experimental SnO2-PS film was compared. The results are as follows: Figure 2 The introduction of P into the PS modification layer significantly improves the visible light transmittance, ensuring the excellent utilization of the device in the visible light band.

[0047] 3. Time-resolved photoluminescence (TRPL) test of perovskite film:

[0048] The performance of perovskite films under different interface layer conditions was compared, namely ITO / SnO2 / PVSK substrate and ITO / SnO2-PS / PVSK substrate. The results showed that the fluorescence lifetime of the PS-modified perovskite film was shortened from 224.3 nanoseconds to 139.1 nanoseconds (see Table 1). The introduction of the PS interface layer effectively suppressed non-radiative recombination and improved the extraction efficiency of carriers at the interface of the electron transport layer.

[0049] Table 1. TRPL life parameters of ITO / SnO2 / PVSK substrate and ITO / SnO2-PS / PVSK substrate

[0050] Films <![CDATA[A1(%)]]> <![CDATA[τ1(ns)]]> <![CDATA[A2(%)]]> <![CDATA[τ2(ns)]]> <![CDATA[τ av (ns)]]> <![CDATA[ITO / SnO2 / PVSK]]> 0.36 55.5 0.63 245.1 224.3 <![CDATA[ITO / SnO2-PS / PVSK]]> 0.70 47.2 0.42 179.4 139.1

[0051] 4. Scanning electron microscopy characterization of perovskite films:

[0052] The surface morphology of the perovskite film was observed by scanning electron microscopy (SEM). Figure 3 ). The results showed that all perovskite films can completely cover the substrate. In contrast, the grain size of the PS-modified perovskite film is larger, mainly because the interaction between potassium ions and perovskite promotes the formation of highly crystalline films. High crystallinity and fewer grain boundaries are conducive to the migration and extraction of carriers, thereby improving device performance.

[0053] 5. Photovoltaic performance test of perovskite devices:

[0054] The unmodified and PS-modified devices were tested using a solar simulator. The results showed that PS modification at an optimal concentration of 5 mg / mL could significantly improve the photovoltaic performance of the device, increasing the energy conversion efficiency from 21.32% to 24.58% (see the attached table for details).

[0055]

Device photovoltaic performance test results list

[0056] PS (mg / mL) <![CDATA[V oc (V)]]> <![CDATA[J sc (mA cm -2 )]]> FF(%) PCE(%) 0 1.13 24.55 76.85 21.32 0.5 1.135 24.68 77.67 21.75 1 1.145 24.96 78.79 22.51 2 1.144 25.10 78.88 22.65 3 1.152 25.23 79.25 23.03 4 1.169 25.36 80.05 23.73 5 1.179 25.67 81.2 24.58 6 1.171 25.54 80.79 24.17

[0057] Experimental results:

[0058] It can be seen from the above test results that the present invention, by introducing the PS bifunctional modifier, passivates the defect states at the interface of SnO2 and perovskite, effectively inhibits interfacial recombination, promotes charge transfer, and significantly improves the performance of PSCs.

[0059] The unique molecular structure and composition characteristics of PS give it multiple synergistic functions: stannate ions can not only passivate the oxygen vacancies on the SnO2 surface, but also adjust the energy level matching between SnO2 and perovskite, and optimize the energy band arrangement of the device. By passivating oxygen defects and improving energy levels, the introduction of PS can also promote the crystallinity of SnO2 film and improve the charge mobility inside and outside the SnO2 layer. At the same time, K + It can effectively promote the crystallization process of the perovskite layer, reduce grain boundary defects, fill the ion vacancies at the A site, and enhance the stability of the perovskite crystal structure. Through the synergistic effect of PS, it is expected to achieve the simultaneous optimization of the interface components of SnO2 and perovskite, and comprehensively improve the photoelectric performance of PSCs.

[0060] The present invention and its embodiments are described above, which is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it and do not deviate from the purpose of the invention, they can creatively design a structure and embodiment similar to the technical solution, which should fall within the protection scope of the present invention.

Claims

1. A method for modifying the buried interface of a perovskite solar cell, characterized in that: The specific steps include: 1) Prepare a solution: dissolve potassium stannate powder in deionized water to prepare an aqueous solution with a concentration of 1-5 mg / mL, and filter; 2) coating: coating the aqueous solution on the tin dioxide film by spin coating; 3) Annealing to form an interface modification layer: The tin dioxide film coated with potassium stannate is annealed to form a potassium stannate interface modification layer.

2. The method for modifying the buried interface of a perovskite solar cell according to claim 1, characterized in that: The potassium stannate structural formula is:

3. The method for modifying the buried interface of a perovskite solar cell according to claim 1, characterized in that: In the step 1), the potassium stannate powder is added into deionized water, stirred at room temperature for 0.5 h, and filtered using a 0.22 μm filter membrane to obtain an aqueous solution.

4. The method for modifying the buried interface of a perovskite solar cell according to claim 1, characterized in that: The spin coating parameters of the spin coating method in step 2) are 3500-4500 rpm, 40-60 s.

5. The method for modifying the buried interface of a perovskite solar cell according to claim 1, characterized in that: The annealing temperature in step 3) is 100° C. and the annealing time is 10 min.

6. The method for modifying the buried interface of a perovskite solar cell according to claim 1, characterized in that: The method also includes the steps of preparing a perovskite active layer, a hole transport layer and a metal electrode on the tin dioxide film.

7. The method for modifying the buried interface of a perovskite solar cell according to claim 6, characterized in that: The perovskite active layer is prepared by a two-step method.

Citation Information

Patent Citations

  • Metal substrate perovskite structure, preparation method and solar cell

    CN115915791A

  • Buried interface modified perovskite solar cell module and preparation method thereof

    CN118139435A

  • Lanthanum-doped barium stannate nanocrystalline implanted TiO2-SnO2 electron transport layer and preparation method and application thereof

    CN119095457A

Cited By

  • Method for modifying buried interface of wide band gap perovskite solar cell and application thereof

    CN122719330A